Penerapan Metode SQ3R dalam Meningkatkan Reading Ability Siswa SMPN 4 Sibulue - A.Tenrinia Asmanur; Ani Astuti; Andi Mulyani; Sukmawati Sukmawati; Kartika Kartika (Jurnal Studi Guru dan Pembelajaran, 2026)
This study aimed to describe the implementation of the SQ3R (Survey, Question, Read, Recite, Review) method in reading instruction and to explore students’ and teacher’s perceptions of its use at SMPN 4 Sibulue. This research employed a qualitative descriptive approach involving twenty students and one English teacher selected through purposive sampling. Data were collected through classroom observation and in-depth interviews focusing on the procedural implementation of the SQ3R method and participants’ responses during the learning process. The research process covered three stages: pre-activities, which focused on observing classroom conditions during the initial implementation of SQ3R; while-activities, which examined the application of each SQ3R step and classroom interactions; and post-activities, which explored students’ and teacher’s perceptions of the method. The findings showed that SQ3R was implemented through systematic reading stages that helped students read texts in a more structured and purposeful way. Students were guided to preview the text, formulate or respond to questions, read to find relevant information, restate key points, and review their understanding. The method also encouraged students’ active participation and helped them focus on important information in the text. However, some students initially experienced difficulties in following the sequence of steps, particularly because the method required more time and repeated reading. Therefore, SQ3R can be considered a useful reading strategy when implemented with clear teacher guidance and gradual habituation.